Effect of Consumer Perception on The Purchase Decision of Children's Football Clothing Products: (Case Study on Shopee at Yuro Sport Store) - Nalindah, Vivi; Chan, Arianis; Tresna, Pratami Wulan; Barkah, Cecep Safa'atul (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
Business competition is getting tougher day by day for both small and large-scale businesses. And the Covid-19 pandemic has also greatly impacted the decline in sales, including the Yuro Sport Store which sells online at Shopee. The owner of the Yuro Sport Store wants to know whether there is a relationship that affects consumer perceptions of the decision to purchase children's soccer clothes at the Yuro Sport Store. By examining consumer perception variables consisting of sensation, organization, and implementation dimensions as well as purchasing decision variables consisting of product choices, brand choices, dealer choices, purchase amounts, purchase timings, and payment methods, researchers used the Pearson correlation test to determine the relationship between the two variables. And the results show the relationship between consumer perceptions of purchasing decisions. Researchers also propose development strategies, including designing attractive product photos on the main display and adding new product lines.